2018
DOI: 10.5194/amt-11-1251-2018
|View full text |Cite
|
Sign up to set email alerts
|

Regional uncertainty of GOSAT XCO<sub>2</sub> retrievals in China: quantification and attribution

Abstract: Abstract. The regional uncertainty of the column-averaged dry air mole fraction of CO2 (XCO2) retrieved using different algorithms from the Greenhouse gases Observing SATellite (GOSAT) and its attribution are still not well understood. This paper investigates the regional performance of XCO2 within a latitude band of 37–42° N segmented into 8 cells in a grid of 5° from west to east (80–120° E) in China, where typical land surface types and geographic conditions exist. The former includes desert, grassland and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…From Figure 8a, it can be found that the dXCO 2 in western area, the desert area of Xinjiang, shows high values even if there are much less anthropogenic emission over this area as shown in Figure 4b. This is likely resulted in the uncertainty of ACOS XCO 2 retrievals in desert which has been indicated by Bie et al [34].…”
Section: Resultsmentioning
confidence: 95%
“…From Figure 8a, it can be found that the dXCO 2 in western area, the desert area of Xinjiang, shows high values even if there are much less anthropogenic emission over this area as shown in Figure 4b. This is likely resulted in the uncertainty of ACOS XCO 2 retrievals in desert which has been indicated by Bie et al [34].…”
Section: Resultsmentioning
confidence: 95%
“…However, the study periods or spatial scales are limited [34,35]. In addition, most scholars focus their research on accuracy/uncertainty analysis [5,36,37], and some studies compared the difference of CO 2 concentration in the same area from different satellites [31,37] or investigated the effect of a single carbon source/sink on the concentration of CO 2 ; for example, the studies of CO 2 emissions from anthropogenic activities [32,38], the impact of vegetable absorption [14,39] and the estimated CO 2 emissions from forest fires [10,40]. However, these studies lack comprehensive consideration of multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters in Eq. (1) are detailed in the study of Bie et al (2018). 0 1 2 3 4 5 (t) A A t A sin 2 t A cos 2 t A sin 4 t A cos 4 t…”
Section: Time Series and Seasonal Trend Of Nh3mentioning
confidence: 99%